The cares in the middle of migration. the social organization of transnational care from a gender perspective - Gonzálvez Torralbo, Herminia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
Throughout this article, It is proposed a theoretical and methodological approach: the social organization of transnational care from a gender perspective. In this article, it is shown that families and social networks related to migration sustain their lives through certain social practices that are cares, which emotional, moral and material dimensions are mainly crossedby gender and kinship. These categories are inseparable from thepower relations in the migration context. Specifically, this is a theoretical and methodological approach that is based on the ethnography of care in migration.
Keywords: Families related to migration; Care; Gender; Colombia; Ethnography